Interaction of human plasma fibronectin with cariogenic and non-cariogenic oral streptococci. - Babu, J P (1983)
The interaction of purified human plasma fibronectin (Fn) with bacteria was studied with a variety of oral streptococci. Each of the strains of Streptococcus mutans, Streptococcus salivarius, Streptococcus sanguis, and Streptococcus mitis tested was aggregated by Fn to various degrees, depending on the concentration of Fn added to the test mixtures. Binding assays performed with radiolabeled Fn and various strains of streptococci demonstrated various capabilities to bind Fn, and the amount of Fn bound by each strain was paralleled by its Fn-induced aggregation, with S. mutans 6715 giving the highest values in both assays. Because of the avid binding of Fn by certain strains of potentially cariogenic streptococci, we investigated the possibility that Fn may be present in human saliva and may be adsorbed from saliva onto artificial tooth pellicles. Immunoreactive Fn was detected in paraffin-stimulated whole saliva by enzyme-linked immunosorbent assays of saliva adsorbed onto gelatin-coated cuvettes and by immunoelectroblots (Western blots) of salivary components separated on sodium dodecyl sulfate-polyacrylamide slab gels. Furthermore, immunoreactive Fn was found to be present in artificial tooth pellicles formed by incubating hydroxyapatite beads with whole human saliva. These results demonstrate that certain strains of oral streptococci bind to and are aggregated by Fn. The presence of Fn in artificial tooth pellicles suggests that this macromolecule may play a role in the attachment of potentially cariogenic and other oral streptococci to dental tissues.